LUMBER YELD IN FUNCTION OF DIAMETER CLASSES AND QUALITY STANDARDS OF LOGS - Silva, Cícero Ramos Pereira da; Latorraca, João Vicente Figueiredo; Carmo, Jair Figueiredo; Mojena, Pastor Amador (Floresta, 2014)
Abstract The objective of this study was to determine and evaluate the yield of four (4) diameter classes in function of quality of logs, in logwood processing of Cedrinho (Erisma uncinatumWarm.). 20 logs of four diameter classes between 46 and 85 cm were selected and classified in terms of quality, being 5 logs for each diameter class. Diameter class I resulted in the lowest yield and diameter class III showed the highest yield. Yield increased according to the diameter of the logs in classes I, II and III. Class IV logs with larger diameters had quality defects such as cracks and internal flaws, causing a small yield drop. It could be concluded that there was a correlation between diameter and yield. Keywords: Mato Grosso; sawmill; native wood; correlation. Resumo Rendimento de madeira serrada em função de classes diamétricas e padrões de qualidade da tora. O objetivo deste trabalho foi determinar e avaliar o rendimento em diferentes classes diamétricas em função da qualidade das toras no desdobro do Cedrinho (Erisma uncinatum Warm.). Foram selecionadas e classificadas quanto à qualidade 20 toras em quatro classes diamétricas, entre 46 e 85 cm, sendo cinco toras para cada classe diamétrica. A classe diamétrica I apresentou o menor rendimento e a classe diamétricaIII apresentou o maior. O rendimento aumentou de acordo com o diâmetro das toras na classe I, II e III. As toras da classe IV, com maiores diâmetros, apresentaram baixa qualidade, com defeitos como rachaduras e falhas internas, causando uma pequena queda no rendimento. Pode-se dizer que existe uma correlação entre diâmetro e rendimento. Palavras-chave: Mato Grosso; serraria; madeira nativa; correlação.